Efforts to Improve Learning Outcomes of Akidah Akhlak Material Clean Heart by Begging for Mercy by Applying the Ctl Learning Model to Class Vi Mi Negeri 3 Jakarta Students for the 2019/2020 Academic Year - Iing Tajudin (Journal of Social Research, 2023)
This research is based on the following problems: (a) Do cooperative learning of the Contextual Teaching and Learning model affect the learning outcomes of Pancasila and Civic Education in Class VI Students? (b) How high is the level of mastery of the subject matter of Pancasila and Civic Education with the application of the Contextual Teaching and Learning model cooperative learning method to Class VI Students? The objectives of this study are: (a) To reveal the influence of cooperative learning of the Contextual Teaching and Learning model on the learning outcomes of Pancasila and Civic Education in Class VI Students. (b) Want to know how far the understanding and mastery of the subjects of Pancasila and Civic Education after the implementation of cooperative learning of the Contextual Teaching and Learning model in Class VI Students This study used three rounds of action research. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this study is Class VII students The data was obtained in the form of portfolio test results and, observation sheets for teaching and learning activities. From the results of the analysts, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (68%), cycle II (76and %), cycle III (96%). The conclusion of this study is that the cooperative method of the Contextual Teaching and Learning model can have a positive effect on the learning motivation of Class VI students, and this learning model can be used as an alternative to Pancasila and Citizenship Education.